Pelatihan Pembuatan Modul Ajar Berbasis Project Based Learning (PjBL) bagi Guru SMPIT Anak Soleh Mataram - Rusman, Januari Rizki Pratama; Chaer, Hasanudin; Ramdhani, Marlinda; Wahyuni, Wika (Pendidikan Matematika, FKIP Universitas Mataram, 2024)
Training on making teaching modules based on Project Based Learning (PjBL) is an effort to improve teacher competence in compiling innovative learning tools that are relevant to the needs of 21st century students. This study aims to evaluate the implementation of the training at SMPIT Anak Soleh Mataram. The research method used is qualitative with a descriptive approach, involving 15 teachers as participants. Data collection was carried out through questionnaires and interviews to measure the level of participant satisfaction and the effectiveness of the training. The results showed that this training received a very positive response from the participants. Based on the questionnaire, the majority of teachers expressed high satisfaction with the quality of the material, delivery methods, and facilitator performance. In addition, all participants succeeded in compiling teaching modules based on PjBL well after participating in the training. In-depth interviews revealed that the training helped teachers understand the principles and steps of implementing PjBL, although some participants identified challenges in implementing the modules in the classroom, such as time management and student involvement. Overall, this training was effective in improving teacher competence in compiling teaching modules based on PjBL. This study recommends further training and implementation assistance to ensure the sustainability of its impact in the learning environment.